The Social and Environmental Responsibilities of Multinationals: Evidence from the Brent Spar Case - Zyglidopoulos, Stelios C. (Journal of business ethics, 2002)
This paper argues that multinational corporations face levels of environmental and social responsibility higher than their national counterparts. Drawing on the literatures of stakeholder salience, corporate reputation management, and evidence from the confrontation between Shell and Greenpeace over the Brent Spar, in 1995, two mechanisms – international reputation side effects, and foreign stakeholder salience – are identified and their contribution in creating an environment more restrictive, in terms of environmental and social responsibility, is elaborated on. The paper concludes with discussing the links of the work presented here with a number of ongoing debates within the filed of international business ethics, and the managerial implications of the two mechanisms identified.